A method for preparing a low-thermal-conductivity, high-heat-retention carbon-carbon composite porous material applicable to various temperatures

CN118745117BActive Publication Date: 2026-10-16SHANXI BEITERUI NEW ENERGY TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410737377.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-07
Publication Date
2026-10-16
Estimated Expiration
2044-06-07

Smart Images

  • Figure CN118745117B_ABST
    Figure CN118745117B_ABST
Patent Text Reader

Abstract

The application relates to a preparation method of low-thermal-conductivity high-thermal-insulation carbon-carbon composite porous material which can be used at various temperatures, and relates to a preparation method of carbon-carbon composite porous material. The application provides a method for preparing porous carbon material by compounding viscose fibers, carbon fibers and graphite fibers, and the pore diameter of the prepared carbon material can be adjusted according to requirements; the compaction material is treated through two steps of carbonization and graphitization, the damage of uncontrolled volatilization of volatile components in the carbonization process to the material structure is avoided, and it is ensured that the carbon-carbon composite porous material with uniform pore diameter distribution is obtained after graphitization. When the porous carbon material prepared by the application is used as thermal insulation material, the thermal conductivity coefficient is not higher than 0.25 W / mK at normal temperature (25 DEG C) and not higher than 0.70 W / mK at high temperature (2000 DEG C). The carbon-carbon composite porous material prepared by the application is used as low-thermal-conductivity thermal insulation material or high-temperature-resistant material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for preparing carbon-carbon composite porous materials. Background Technology

[0002] With social development and technological progress, an increasing number of new material research and development and production processes require high temperatures. Therefore, thermal insulation materials suitable for use at various temperatures, especially higher temperatures, have become indispensable basic materials in modern industrial technology, playing a vital role in glass, ceramics, crystal growth, and the development of many other new materials.

[0003] Carbon / graphite materials have good physical and chemical stability and excellent thermal shock resistance, and have long been used in thermal shock and corrosion resistant refractory materials. They are widely used as furnace lining materials for converters, electric furnaces, ladles and other furnaces used in iron and steel smelting.

[0004] Porous materials play an important role in thermal insulation materials, and the porosity and distribution of the material have a significant impact on the thermal insulation performance.

[0005] Currently, existing high-temperature insulation materials have drawbacks such as high thermal conductivity, poor stability at high temperatures, difficulty in accurately controlling the pore density and material density of porous materials, poor strength, and short service life.

[0006] Therefore, developing porous carbon materials with lower thermal conductivity, adjustable porosity and density, and certain strength is of great practical significance. Summary of the Invention

[0007] This invention addresses the shortcomings and drawbacks of existing technologies by providing a method for preparing low thermal conductivity and high heat insulation carbon-carbon composite porous materials that can be used at various temperatures.

[0008] A method for preparing a low thermal conductivity, high heat insulation carbon-carbon composite porous material that can be used at various temperatures is specifically carried out according to the following steps:

[0009] I. Carbonization:

[0010] First, viscose fibers are loaded into a high-temperature furnace filled with protective gas. Then, the high-temperature furnace is heated to 600℃~800℃ and carbonized at 600℃~800℃ for a period of time to obtain carbon fibers.

[0011] 2. The viscose fiber, the carbon fiber and graphite fiber prepared in step 1 are respectively prepared into short fibers to obtain viscose short fibers, carbon short fibers and graphite short fibers.

[0012] 3. Remove magnetic particles from the materials by passing the viscose short fiber, carbon short fiber and graphite short fiber through a demagnetizer, and then mix them with the resin in the mixer according to the required proportions to obtain a mixture.

[0013] 4. Fill the mixture obtained in step 3 into the mold and press it to obtain the pressed mixture;

[0014] 5. Place the molded mixture into a box furnace for curing to obtain the cured molded block;

[0015] 6. The cured molding block is placed in a carbonization furnace for carbonization, and then the carbonized molding block is placed in a graphitization furnace for graphitization treatment to obtain a low thermal conductivity and high heat insulation carbon-carbon composite porous material that can be used at various temperatures.

[0016] The beneficial effects of this invention are:

[0017] 1. This invention provides a method for preparing porous carbon materials using a composite of viscose fiber, carbon fiber and graphite fiber, wherein the pore size of the prepared carbon material can be adjusted as needed;

[0018] 2. This invention processes the molding material through two steps: carbonization and graphitization. This avoids the damage to the material structure caused by the uncontrolled release of volatiles during the carbonization process, and ensures that the carbon-carbon composite porous material with uniform pore size distribution is obtained after graphitization.

[0019] 3. This invention can achieve controllable preparation of porous carbon materials by adjusting factors such as raw material size and ratio, which can expand the application fields and scope of the porous carbon materials.

[0020] 4. When the porous carbon material prepared by this invention is used as a thermal insulation material, its thermal conductivity is not higher than 0.25 W / mK at room temperature (25℃) and not higher than 0.70 W / mK at high temperature (2000℃).

[0021] 5. The porous carbon material prepared by this invention can be processed into the required size and shape according to the needs of different application scenarios, making it convenient to use;

[0022] 6. The porous carbon material prepared by this invention can be used in high-temperature applications with temperatures up to 3000℃, has stable physicochemical properties, is suitable for applications with high environmental requirements, and has a long service life. Attached Figure Description

[0023] Figure 1 This is an SEM image of the viscose fiber described in step one of Example 1;

[0024] Figure 2 SEM image of the low thermal conductivity, high thermal insulation carbon-carbon composite porous material prepared in Example 1, which can be used at various temperatures;

[0025] Figure 3The thermal conductivity test results of the low thermal conductivity and high heat insulation carbon-carbon composite porous material prepared in Example 1, which can be used at various temperatures, at different temperatures;

[0026] Figure 4 SEM image of the carbon-carbon composite porous material prepared in Comparative Example 1;

[0027] Figure 5 SEM image of the low thermal conductivity, high heat insulation carbon-carbon composite porous material prepared in Example 2 that can be used at various temperatures;

[0028] Figure 6 SEM image of the low thermal conductivity, high heat insulation carbon-carbon composite porous material prepared in Example 3, which can be used at various temperatures. Detailed Implementation

[0029] Specific Implementation Method 1: This implementation method provides a method for preparing a low thermal conductivity, high heat insulation carbon-carbon composite porous material that can be used at various temperatures. The method is specifically completed according to the following steps:

[0030] I. Carbonization:

[0031] First, viscose fibers are loaded into a high-temperature furnace filled with protective gas. Then, the high-temperature furnace is heated to 600℃~800℃ and carbonized at 600℃~800℃ for a period of time to obtain carbon fibers.

[0032] 2. Viscose fiber, carbon fiber and graphite fiber prepared in step 1 are respectively prepared into short fibers to obtain viscose short fibers, carbon short fibers and graphite short fibers.

[0033] 3. Remove magnetic particles from the materials by passing the viscose short fiber, carbon short fiber and graphite short fiber through a demagnetizer, and then mix them with the resin in the mixer according to the required proportions to obtain a mixture.

[0034] 4. Fill the mixture obtained in step 3 into the mold and press it to obtain the pressed mixture;

[0035] 5. Place the molded mixture into a box furnace for curing to obtain the cured molded block;

[0036] 6. The cured molding block is placed in a carbonization furnace for carbonization, and then the carbonized molding block is placed in a graphitization furnace for graphitization treatment to obtain a low thermal conductivity and high heat insulation carbon-carbon composite porous material that can be used at various temperatures.

[0037] Specific Implementation Method Two: This implementation method differs from Specific Implementation Method One in that the protective gas mentioned in step one is one or a mixture of two of nitrogen and argon. The other steps are the same as in Specific Implementation Method One.

[0038] Specific Implementation Method Three: This implementation method differs from Specific Implementation Method One or Two in that: the heating rate in step one is 50℃ / h to 55℃ / h; the carbonization time in step one is no less than 10h. Other steps are the same as in Specific Implementation Method One or Two.

[0039] Specific Implementation Method Four: This implementation method differs from Specific Implementation Methods One to Three in that: the size of the viscose short fibers mentioned in step two is 4mm to 8mm; the size of the carbon short fibers mentioned in step two is 5mm to 9mm; and the size of the graphite short fibers mentioned in step two is 2mm to 5mm. The other steps are the same as in Specific Implementation Methods One to Three.

[0040] Specific Implementation Method Five: This implementation method differs from Specific Implementation Methods One to Four in that the mass ratio of viscose short fibers, carbon short fibers, and graphite short fibers in step three is (10-20):(40-80):(10-40). The other steps are the same as in Specific Implementation Methods One to Four.

[0041] Specific Implementation Method Six: This implementation method differs from Specific Implementation Methods One to Five in that the mass of the resin mentioned in step three accounts for 10% to 30% of the total mass of viscose short fibers, carbon short fibers, and graphite short fibers. The other steps are the same as in Specific Implementation Methods One to Five.

[0042] Specific Implementation Method Seven: This implementation method differs from Specific Implementation Methods One through Six in that the resin mentioned in step three is phenolic resin, acrylic resin, or polyurethane resin. The other steps are the same as in Specific Implementation Methods One through Six.

[0043] Specific Implementation Method Eight: This implementation method differs from Specific Implementation Methods One to Seven in that the curing temperature in step five is 200℃~210℃, and the curing time is no less than 100 hours. The other steps are the same as in Specific Implementation Methods One to Seven.

[0044] Specific Implementation Method Nine: This implementation method differs from Specific Implementation Methods One to Eight in that: the carbonization temperature in step six is ​​600℃~800℃, and the carbonization time is not less than 50 hours; the graphitization temperature in step six is ​​2200℃~2500℃, and the graphitization time is not less than 72 hours. The other steps are the same as in Specific Implementation Methods One to Eight.

[0045] Specific Implementation Method 10: This implementation method is a low thermal conductivity, high heat insulation carbon-carbon composite porous material that can be used as a low thermal conductivity heat insulation material or a high temperature resistant material, which can be used at various temperatures.

[0046] The beneficial effects of the present invention are verified using the following embodiments:

[0047] Example 1: A method for preparing a low thermal conductivity, high heat insulation carbon-carbon composite porous material that can be used at various temperatures, specifically comprising the following steps:

[0048] I. Carbonization:

[0049] First, viscose fiber is loaded into a high-temperature furnace filled with nitrogen. Then, the high-temperature furnace is heated to 700°C at a heating rate of 50°C / h. The fiber is then carbonized at 700°C for 10 hours to obtain carbon fiber.

[0050] 2. Using a crusher, viscose fiber, carbon fiber and graphite fiber prepared in step 1 are respectively processed into short fibers to obtain viscose short fibers, carbon short fibers and graphite short fibers.

[0051] The viscose staple fiber mentioned in step two has a size of 5 mm;

[0052] The carbon short fibers mentioned in step two have a size of 7 mm;

[0053] The graphite short fibers mentioned in step two have a size of 4 mm;

[0054] 3. Remove magnetic particles from the materials by passing the viscose short fiber, carbon short fiber and graphite short fiber through a demagnetizer, and then mix them with phenolic resin particles (PR12603) in a mixer according to the required proportions to obtain a mixture.

[0055] The mass ratio of viscose short fibers, carbon short fibers and graphite short fibers mentioned in step three is 10:50:40;

[0056] The phenolic resin mentioned in step three accounts for 15% of the total mass of viscose short fibers, carbon short fibers and graphite short fibers;

[0057] 4. Fill the mixture obtained in step 3 into the mold and press it to obtain the pressed mixture;

[0058] The dimensions of the mold mentioned in step four are 50cm × 30cm × 20cm;

[0059] 5. Place the molded mixture into a box furnace for curing to obtain the cured molded block;

[0060] The curing temperature in step five is 210℃, and the curing time is 110h.

[0061] 6. The cured molding block is placed in a carbonization furnace for carbonization, and then the carbonized molding block is placed in a graphitization furnace for graphitization treatment to obtain a low thermal conductivity and high heat insulation carbon-carbon composite porous material that can be used at various temperatures.

[0062] The carbonization temperature described in step six is ​​700℃, and the carbonization time is 60 hours.

[0063] The graphitization process described in step six is ​​carried out at a temperature of 2500℃ for 72 hours.

[0064] Figure 1 This is an SEM image of the viscose fiber described in step one of Example 1;

[0065] Figure 2 SEM image of the low thermal conductivity, high thermal insulation carbon-carbon composite porous material prepared in Example 1, which can be used at various temperatures;

[0066] from Figure 1 It can be seen that viscose fiber raw material is long fiber with uniform diameter, smooth surface, and appears to be randomly stacked.

[0067] from Figure 2 It can be seen that in the prepared carbon-carbon composite porous material, the carbon fiber size is about 20-100μm, and the short fibers are bonded and stacked together to form a porous structure.

[0068] The low thermal conductivity and high heat insulation carbon-carbon composite porous material prepared in Example 1, which can be used at various temperatures, was cut into 50×50×20mm pieces. 3 The thermal conductivity of the test sample block was measured at room temperature (25℃), 400℃, 800℃, 1200℃, 1600℃, and 2000℃. Figure 3 These are the results of thermal conductivity tests.

[0069] Figure 3 The thermal conductivity test results of the low thermal conductivity and high heat insulation carbon-carbon composite porous material prepared in Example 1, which can be used at various temperatures, at different temperatures;

[0070] Test results show that the thermal conductivity of the carbon-carbon composite porous material prepared by this invention increases with increasing test temperature. The thermal conductivity at room temperature is 0.21 W / mK (see Table 1), and the thermal conductivity at 2000℃ is 0.61 W / mK.

[0071] Comparing with Example 1: The preparation method of carbon-carbon composite porous materials is specifically carried out according to the following steps:

[0072] I. Carbonization:

[0073] First, viscose fiber is loaded into a high-temperature furnace filled with nitrogen. Then, the high-temperature furnace is heated to 700°C at a heating rate of 50°C / h. The fiber is then carbonized at 700°C for 10 hours to obtain carbon fiber.

[0074] 2. Using a crusher, viscose fiber, carbon fiber and graphite fiber prepared in step 1 are respectively processed into short fibers to obtain viscose short fibers, carbon short fibers and graphite short fibers.

[0075] The viscose staple fiber mentioned in step two has a size of 9 mm;

[0076] The carbon short fibers mentioned in step two have a size of 9 mm;

[0077] The graphite short fibers mentioned in step two have a size of 6 mm;

[0078] 3. Remove magnetic particles from the materials by passing the viscose short fiber, carbon short fiber and graphite short fiber through a demagnetizer, and then mix them with phenolic resin particles (PR12603) in a mixer according to the required proportions to obtain a mixture.

[0079] The mass ratio of viscose short fibers, carbon short fibers and graphite short fibers mentioned in step three is 30:50:20;

[0080] The phenolic resin mentioned in step three accounts for 15% of the total mass of viscose short fibers, carbon short fibers and graphite short fibers;

[0081] Fourth, the mixture obtained in step three is filled into the mold through a feeding device and pressed to obtain the pressed mixture.

[0082] The dimensions of the mold mentioned in step four are 50cm × 30cm × 20cm;

[0083] 5. Place the molded mixture into a box furnace for curing to obtain the cured molded block;

[0084] The curing temperature in step five is 210℃, and the curing time is 110h.

[0085] 6. The cured molding block is placed in a carbonization furnace for carbonization, and then the carbonized molding block is placed in a graphitization furnace for graphitization treatment to obtain a low thermal conductivity and high heat insulation carbon-carbon composite porous material that can be used at various temperatures.

[0086] The carbonization temperature described in step six is ​​700℃, and the carbonization time is 60 hours.

[0087] The graphitization process described in step six is ​​carried out at a temperature of 2500℃ for 72 hours.

[0088] Figure 4 SEM image of the carbon-carbon composite porous material prepared in Comparative Example 1;

[0089] from Figure 4 It can be seen that the carbon-carbon composite porous material prepared in Comparative Example 1 exhibits a relatively obvious agglomeration phenomenon.

[0090] The carbon-carbon composite porous material prepared in Comparative Example 1 has a thermal conductivity of 0.35 W / mK at room temperature (see Table 1).

[0091] Comparing with Example 2: The preparation method of carbon-carbon composite porous materials is specifically carried out according to the following steps:

[0092] I. Carbonization:

[0093] First, viscose fiber is loaded into a high-temperature furnace filled with nitrogen. Then, the high-temperature furnace is heated to 700°C at a heating rate of 50°C / h. The fiber is then carbonized at 700°C for 10 hours to obtain carbon fiber.

[0094] 2. Using a crusher, polyester fiber, carbon fiber and graphite fiber prepared in step 1 are respectively processed into short fibers to obtain polyester short fibers, carbon short fibers and graphite short fibers.

[0095] The polyester staple fiber mentioned in step two has a size of 5 mm;

[0096] The carbon short fibers mentioned in step two have a size of 7 mm;

[0097] The graphite short fibers mentioned in step two have a size of 4 mm;

[0098] 3. Polyester short fibers, carbon short fibers and graphite short fibers are respectively demagnetized to remove magnetic particles from the materials, and then mixed with phenolic resin particles (PR12603) in a mixer according to the required proportions to obtain a mixture.

[0099] The mass ratio of polyester staple fiber, carbon staple fiber and graphite staple fiber mentioned in step three is 10:50:40;

[0100] The phenolic resin mentioned in step three accounts for 15% of the total mass of viscose short fibers, carbon short fibers and graphite short fibers;

[0101] Fourth, the mixture obtained in step three is filled into the mold through a feeding device and pressed to obtain the pressed mixture.

[0102] The dimensions of the mold mentioned in step four are 50cm × 30cm × 20cm;

[0103] 5. Place the molded mixture into a box furnace for curing to obtain the cured molded block;

[0104] The curing temperature in step five is 210℃, and the curing time is 110h.

[0105] 6. Place the cured molded block into a carbonization furnace for carbonization; after carbonization, cool to room temperature;

[0106] The carbonization temperature described in step six is ​​700℃, and the carbonization time is 60 hours.

[0107] During the carbonization process described above, the polyester fibers in the cured molded block melt and decompose, producing an aromatic odor and black smoke. Subsequent processes are difficult to carry out, and a porous structure cannot be effectively formed, resulting in the failure to obtain carbon-carbon composite porous materials.

[0108] Example 2: The difference between this example and Example 1 is that the size of the viscose short fiber in step two is 6 mm; the size of the carbon short fiber in step two is 8 mm; the size of the graphite short fiber in step two is 4 mm; the mass ratio of viscose short fiber, carbon short fiber and graphite short fiber in step three is 20:40:40; the mass of the phenolic resin in step three accounts for 20% of the total mass of viscose short fiber, carbon short fiber and graphite short fiber. Other steps and parameters are the same as in Example 1.

[0109] Figure 5 SEM image of the low thermal conductivity, high heat insulation carbon-carbon composite porous material prepared in Example 2 that can be used at various temperatures;

[0110] from Figure 5 It can be seen that the low thermal conductivity and high heat insulation carbon-carbon composite porous material prepared in Example 2, which can be used at various temperatures, is almost the same as that in Example 1 and is at the same level.

[0111] The room temperature thermal conductivity of the carbon-carbon composite porous material prepared in Example 2 was 0.22 W / mK, which is almost the same as that in Example 1, and is at the same level.

[0112] Example 3: The difference between this example and Example 1 is as follows: In step one, viscose fibers are first loaded into a high-temperature furnace filled with nitrogen and argon (the volume ratio of nitrogen to argon is 9:1). Then, the high-temperature furnace is heated to 700°C at a heating rate of 50°C / h, and then carbonized at 700°C for 10 hours to obtain carbon fibers. In step two, the size of the viscose short fibers is 4 mm; the size of the carbon short fibers in step two is 5 mm; the size of the graphite short fibers in step two is 3 mm. In step three, the mass ratio of viscose short fibers, carbon short fibers, and graphite short fibers is 10:80:10. In step three, the mass of phenolic resin accounts for 20% of the total mass of viscose short fibers, carbon short fibers, and graphite short fibers. Other steps and parameters are the same as in Example 1.

[0113] Figure 6 SEM image of the low thermal conductivity, high heat insulation carbon-carbon composite porous material prepared in Example 3 that can be used at various temperatures;

[0114] from Figure 6It can be seen that the low thermal conductivity and high heat insulation carbon-carbon composite porous material prepared in Example 3, which can be used at various temperatures, is almost the same as that in Example 1 and is at the same level.

[0115] The room temperature thermal conductivity of the carbon-carbon composite porous material prepared in Example 2 was 0.22 W / mK, which is almost the same as that in Example 1, and is at the same level.

[0116] Table 1

[0117]

Claims

1. A method for preparing a low thermal conductivity, high heat insulation carbon-carbon composite porous material applicable at various temperatures, characterized in that... The preparation method is specifically carried out according to the following steps: I. Carbonization: First, viscose fibers are loaded into a high-temperature furnace filled with protective gas. Then, the furnace is heated to 600℃~800℃ and carbonized at 600℃~800℃ for a period of time to obtain carbon fibers.

2. The viscose fiber, the carbon fiber and graphite fiber prepared in step 1 are respectively prepared into short fibers to obtain viscose short fibers, carbon short fibers and graphite short fibers. The size of the viscose short fibers mentioned in step two is 4mm~8mm; the size of the carbon short fibers mentioned in step two is 5mm~9mm; the size of the graphite short fibers mentioned in step two is 2mm~5mm.

3. Remove magnetic particles from the materials by passing the viscose short fiber, carbon short fiber and graphite short fiber through a demagnetizer, and then mix them with the resin in the mixer according to the required proportions to obtain a mixture. The mass ratio of viscose short fiber, carbon short fiber and graphite short fiber mentioned in step three is (10~20):(40~80):(10~40); The resin mentioned in step three accounts for 10% to 30% of the total mass of viscose short fibers, carbon short fibers, and graphite short fibers; 4. Fill the mixture obtained in step 3 into the mold and press it to obtain the pressed mixture; 5. Place the molded mixture into a box furnace for curing to obtain the cured molded block; 6. The cured molding block is placed in a carbonization furnace for carbonization, and then the carbonized molding block is placed in a graphitization furnace for graphitization treatment to obtain a low thermal conductivity and high heat insulation carbon-carbon composite porous material that can be used at various temperatures. The carbonization temperature in step six is ​​600℃~800℃, and the carbonization time is not less than 50h; the graphitization temperature in step six is ​​2200℃~2500℃, and the graphitization time is not less than 72h.

2. The method for preparing a low thermal conductivity, high heat insulation carbon-carbon composite porous material applicable at various temperatures according to claim 1, characterized in that... The protective gas mentioned in step one is one or a mixture of two of nitrogen and argon.

3. The method for preparing a low thermal conductivity, high heat insulation carbon-carbon composite porous material applicable at various temperatures according to claim 1, characterized in that... The heating rate described in step one is 50℃ / h ~ 55℃ / h; the carbonization time described in step one is not less than 10h.

4. The method for preparing a low thermal conductivity, high heat insulation carbon-carbon composite porous material applicable at various temperatures according to claim 1, characterized in that... The resin mentioned in step three is phenolic resin, acrylic resin, or polyurethane resin.

5. The method for preparing a low thermal conductivity, high heat insulation carbon-carbon composite porous material applicable at various temperatures according to claim 1, characterized in that... The curing temperature in step five is 200℃~210℃, and the curing time is no less than 100h.

6. The application of a low thermal conductivity, high heat insulation carbon-carbon composite porous material prepared by the preparation method according to claim 1, which can be used at various temperatures, is characterized in that... A low thermal conductivity, high thermal insulation carbon-carbon composite porous material that can be used at various temperatures as a low thermal conductivity thermal insulation material or a high temperature resistant material.

Citation Information

Patent Citations

  • Compound thermal insulation material manufactured by using waste fibers and manufacturing method thereof

    CN103467000A

  • Carbon-based material for thermal insulation device

    CN111763096A